2019
DOI: 10.1287/trsc.2019.0908
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Traffic Dynamics Under Fast-Varying Demand

Abstract: Aggregated dynamic traffic models based on the Network Macroscopic Fundamental Diagram (MFD) have been founded on stationary or steady-state approximations. Theoretically, they are only qualified with slow-varying demand profiles as inputs. In practice, MFD models are often fed with fast-varying demand patterns classically observed during peak hours. This paper investigates the accuracy of existing MFD model outputs in such a case. It also provides a fresh look at hysteresis loops that may arise on MFD shapes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…As proposed in Leclercq and Paipuri, and Mariotte and Leclercq(18,26), the outflow (or trip completion rate) is bounded by the maximum capacity and to sustain the outflow to maximum capacity when network reaches saturation to avoid the causality effect (see e.g., Merchant and Nemhauser, Friesz et al…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As proposed in Leclercq and Paipuri, and Mariotte and Leclercq(18,26), the outflow (or trip completion rate) is bounded by the maximum capacity and to sustain the outflow to maximum capacity when network reaches saturation to avoid the causality effect (see e.g., Merchant and Nemhauser, Friesz et al…”
mentioning
confidence: 99%
“…Mahmassani et al showed that higher demand during congestion period results in the larger hysteresis loop in the MFD ( 17 ). Recently, Leclercq and Paipuri proposed a deeper investigation of the clockwise hysteresis phenomenon in the p-MFD by deriving the Lighthill–Whitham–Richards (LWR) solutions to an arterial case with internal bottleneck ( 18 ). They showed that when the network state is close to saturation, the congestion dynamics caused by bottlenecks with unequal shockwave speeds triggers the hysteresis shape in p-MFD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another critical factor to consider while defining the functional fit is the scatter in the data. It was already shown the existence of the hysteresis phenomenon in the case of 2D-MFD due to various factors like network heterogeneity, demand pattern (Buisson and Ladier, 2009;Leclercq and Paipuri, 2019). A framework to account for this hysteresis phenomenon in the MFD modeling framework was proposed in Paipuri et al (2019).…”
Section: City Centermentioning
confidence: 99%
“…The method of cuts introduced by Daganzo and Geroliminis (2008) estimates the MFD for a homogeneous ring road based on VT. Accordingly, related extensions and studies also refer and exploit VT (Boyaci and Geroliminis, 2011;Leclercq and Geroliminis, 2013;Laval and Castrillón, 2015;Tilg et al, 2020;Daganzo and Knoop, 2016;Leclercq and Paipuri, 2019;Girault et al, 2016;Ambühl et al, 2018;Loder et al, 2019). Again, these approximation methods apply VT only at the corridor level, even when trying to estimate traffic conditions at the network level.…”
Section: Introductionmentioning
confidence: 99%